Alat Deteksi Jatuh Berbiaya Murah Dengan Tracking Position Untuk Pasien Vertigo dan Sinkop - Yulastri; Era Madona; Muhammad irmansyah; Anggara Nasution (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
In this study we propose a low-cost portable device to monitor the vertigo and syncope patients whether normal, dizziness or falls. The purpose of this study is design and manufactures a device using an accelerometer sensor to determining the condition of patients who are at risk of vertigo and syncope. The patient's condition is detected by accelerometer which read the values of the x, y and z axes to determine condition normal, dizzy, or fall. This device also uses a real time clock to remind the patient to take medication three times a day. The device outputs are LCD Oled, Voice, and SMS notification. If the patient condition is falls an SMS notification will be sent, the dizzy condition vertigo patient will press the panic button first and then an SMS notification will be sent. The results of tests carried out on the equipment can send SMS and phone calls at an angle of (50o - 70o) = Y (40o - 20o) = X, in a fainting state and falling. The test results of the navigation module prove that the GPS module can determine the exact location by moving the GPS module reading position to a small test point with an average of 2.97 meters.